OUTCOME OF INTRAMEDULLARY SPINAL CORD TUMOURS: EXPERIENCE WITH 18 PATIENTS OPERATED AT AYUB TEACHING HOSPITAL, ABBOTTABAD - Bhatti, Sajid Nazir; Khan, Shahbaz Ali; Raja, Riaz A.; Shah, Rizwan; Aurangzeb, Ahsan; Khan, Abdul Aziz; Alvi, Nazir; Pasha, Muhammad Tousif (Journal of Ayub Medical College Abbottabad, 2010)
Background: Intramedullary spinal cord tumours (IMSCT) are among the uncommon lesions at spinal cord. They can present with a vast array of symptoms and cause severe neurological deficits. With advent and frequent use of MRI more and more patients with IMSCT are picked up. By using modern microsurgical techniques better surgical outcome is achieved. The Objective was to analyse the surgical outcome of the patients with intramedullary Spinal Tumour operated at Ayub Teaching Hospital (ATH), Abbottabad. Methods: Eighteen patients with IMSCT who presented at Neurosurgery Unit, ATH, Abbottabad during 2000-2010 were included in this study. Patients were diagnosed on the basis of MRI. They were operated using standard microsurgical techniques. Patients were followed up for a mean duration of 18 months after surgery and their preoperative and postoperative neurological status was analysed. Results: Patients with age group ranging from 15-50 (37.72±8.94) years with IMSCT were operated. Sixty-one percent of the patients were male and 39% were female. The region most commonly affected was cervical (44%) followed by conus medullaris (33%), cervicothoracic and thoracic each had frequency of 11%. Gross total removal (>95%) was possible in 72% of cases while in rest of 28% cases resection of 80-95% was possible. Histologically 38.9% of the lesions were ependymomas, 27.8% were astrocytomas and 22.2% were teratomas. Neurofibromas and Primitive Neuroectodermal Tumours (PNET) each accounted for 5.5% of the cases. Overall postoperative neurology improved in 10 (55%) of patients, remained unchanged in 5 (27%) of cases, and deteriorated in 3 (16%) patients. One patient was lost in follow-up. Surgery on tumours in cervical and thoracic region carried a relatively poor outcome as compared to the lesion of conus. There were no deaths due to surgery. Conclusion: Surgical removal of IMSCT is beneficial to patients with acceptable surgical risk. Better outcome is expected if the patients with good Frankel grade are diagnosed and operated early the course of disease. Keywords: Spinal tumours, Intramedullary spinal tumour, Ependymoma